2020
DOI: 10.1042/bsr20200124
|View full text |Cite
|
Sign up to set email alerts
|

Potential targets and molecular mechanism of miR-331-3p in hepatocellular carcinoma identified by weighted gene coexpression network analysis

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumor. miR-331-3p has been reported relevant to the progression of HCC, but the molecular mechanism of its regulation is still unclear. In the study, we comprehensively studied the role of miR-331-3p in HCC through weighted gene coexpression network analysis (WGCNA) based on The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO) and Oncomine. WGCNA was applied to build gene co-expression networks to examine the correlation between gene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Qin et al had demonstrated DARS2 as a hepatocarcinoma gene that could promote the progression of hepatocarcinoma cell cycle and inhibit the apoptosis of hepatocarcinoma cells [40]. EFTUD2 gene expression was upregulated in hepatocarcinoma, and had prognostic signi cance in patients with hepatocarcinoma [41]. Liu et al found the expression of FTO in esophageal squamous cell carcinoma (ESCC) to be higher than in adjacent normal tissues, and the corresponding survival curve showed the high expression of FTO to tend toward poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Qin et al had demonstrated DARS2 as a hepatocarcinoma gene that could promote the progression of hepatocarcinoma cell cycle and inhibit the apoptosis of hepatocarcinoma cells [40]. EFTUD2 gene expression was upregulated in hepatocarcinoma, and had prognostic signi cance in patients with hepatocarcinoma [41]. Liu et al found the expression of FTO in esophageal squamous cell carcinoma (ESCC) to be higher than in adjacent normal tissues, and the corresponding survival curve showed the high expression of FTO to tend toward poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhonglin Lv et al found that myeloid loss of EFTUD2 led to impaired activation of macrophage NF-κB and ERK, which reduced the release of pro-inflammatory cytokines and growth factors, and ultimately inhibited tumor development and progression [ 24 ]. A recent study showed that the expressions of COPZ1 and EFTUD2 were significantly higher in tumor tissues compared with normal tissues and both two genes may correlated with poor prognosis of liver cancer based on the TCGA database [ 25 ]. GAPDH is regulated by several cancer-related factors, and its overexpression is an event downstream of p53.…”
Section: Discussionmentioning
confidence: 99%
“…Preparing the matrix of the RNA-seq of the above 105 overlapping genes at rst, the corresponding clinical data were screened according to the expression matrix. The analysis procedure was performed, as described previously [11]. First, the coexpression construction network of overlapping genes; Then, Screening gene modules; Last, identify key genes.…”
Section: Important Module and Key Genes Sorted By Wgcnamentioning
confidence: 99%
“…By integrating data from databases containing TCMSP, BATMAN-TCM, SymMap, STITCH, SEA, Swiss, and PharmMapper, the Cancer Genome Atlas (TCGA), we obtained the overlapping target genes of Tanshinone IIA against HCC. RNA-seq data of the overlapping genes and the related clinical information of Hepatocellular carcinoma (HCC) from TCGA were used for weighted gene co-expression network analysis (WGCNA), which was an analysis method to set up a gene co-expression network among the interested genes to extract the associations between gene modules and speci c clinical properties [11]. To further estimate the genes connections, the genes of the important module were analyzed for the PPI network using Cytoscape.…”
Section: Introductionmentioning
confidence: 99%